Pengaru Kepemimpinan Terhadap Kedisiplinan Aparatur Sipil Negara Di Dinas Sosial Kabupaten Kolaka - Ningsih, Sukma Ayu; Madani, Muhlis; Parawu, Hafiz Elfiansyah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
With this study aims to see and analyze the influence of leadership on the discipline of state civil servants in the social services of Kolaka district. This type of research is a survey research that describes quantitative analysis. The data techniques used were questionnaires and documentation. The data were analyzed descriptively quantitatively using the SPSs application. The sample was 40 people. The results of this study are that there is an influence between the leadership of the state civil apparatus in the district social service which has shown that the leadership of the state civil apparatus in the social service of the Kolaka district is in the category of good assessment, namely 77, 36%, Discipline. The state civil apparatus in the social service of Kolaka district can be seen in Table 4.41 which shows that the discipline of the civil state apparatus in the social service of Kolaka Regency is in the good order category, which is 74.63%, the analysis results show a value or relationship (R) of 0.819. The big influence of the independent variable or leadership (X) on the dependent variable or discipline (Y) which shows the R value of 0.819 which means 90% of the influence of the independent variable or leadershipKeywords: Leadership, Discipline of the State Civil Apparatus